Organizational Factors that influence Implementation of Strategic Plans in Private Secondary Schools in Nairobi - Nyagemi, Abel; Njeru, Winnie; Kinyua, Jesse (Scholars Academic and Scientific Publishers (SAS Publishers), 2017)
The study sought to establish organizational factors influencing implementation of strategic plans in private secondary schools Nairobi. Specifically, the study aimed at determining the effects of top management commitment, coordination of activities, employee skills and responsibilities and organization culture on implementation of strategic plans. A descriptive cross sectional study was used. The study population was 101 private secondary schools. A random sample of 50 private secondary schools was considered. A structured questionnaire was administered. Data was analyzed using inferential and descriptive statistics such as frequencies; percentages and graphs. Exploratory factor analysis was used in determining the influencing factors. The study established the following group of organizational factors as having an influence on implementation of strategic plans in private secondary schools in Nairobi: resource constraints (human and financial), overlapping activities, interference from the local government, work pressure, conflict of interest, poor attitude, overlapping plans and tight timeframes. The conceptual model was tested and found to be having a statistically significant relationship among the implementation of strategic plans, top management commitment, coordination of activities, employee skills and responsibilities and organization culture. The study recommends a further study on the specific factors should be done in particular sub-counties to explicate on how those factors affect implementation of strategic management plans in private schools in other counties in Kenya.
Keywords: Strategy; Strategic Plan; Stakeholders; Organizational Culture; Organizational Culture; Management; Implementation; Culture; Communication